DESENTRALISASI FISKAL DAN KEMANDIRIAN DAERAH PEMEKARAN: STUDI KASUS PADA PROVINSI SULAWESI BARAT - Alih Aji Nugroho; Cindy Candrawati (Dialogue : Jurnal Ilmu Administrasi Publik, 2025)
This paper aims to analyze fiscal decentralization and regional autonomy specifically for new expansion. It begins with a discussion from a theoretical perspective and is then followed by an analysis of fiscal decentralization and regional autonomy, a case study of West Sulawesi Province as one of the provinces resulting from expansion in Indonesia. The method used is a quantitative approach by analyzing the Degree of Decentralization, PAD Effectiveness Ratio, Revenue Growth and analysis of Regional Government Expenditure. The results show that West Sulawesi Province is dominated by the contribution of the central government in the form of balancing funds. In addition, high regional government spending for consumption compared to investment reduces fiscal space to encourage economic growth. Expenditure autonomy will be less effective if spending is allocated primarily for less productive activities. The main challenge of fiscal decentralization in Indonesia is no longer providing as much funding as possible to regions, but how to ensure that regional governments can use the available funds wisely to improve community welfare.